Is there a new climate politics? Emergency, Engagement and Justice, - Davies, Anna (My University, 2021)
Addressing climate change globally requires significant transformations of production and consumption systems. The language around climate action has shifted tangibly over the last five years to reflect this. Indeed, thousands of local governments, national governments, universities and scientists have declared a climate emergency. Some commentators argue that the emergency framing conveys a new and more appropriate level of urgency needed to respond to climate challenges; to create a social tipping point in the fight against climate change. Others are concerned to move on from such emergency rhetoric to urgent action. Beyond emergency declarations, new spaces of, and places for, engagement with climate change are emerging. The public square, the exhibition hall, the law courts, and the investors’ forum are just some of the arenas where climate change politics are now being negotiated. Emergent governing mechanisms are being utilised, from citizens’ assemblies to ecocide lawsuits. New social movements from Extinction Rebellion to Fridays For Future demonstrate heightened concern and willingness to undertake civil disobedience and protest against climate inaction. Yet questions remain which are addressed in this thematic issue: Are these discourses and spaces of engagement manifestations of a radical new climate politics? And if these are new climate politics, do they mark a shift of gear in current discourses with the potential to effect transformative climate action and support a just transition to a decarbonised world?
PUBLISHED
Keywords: Climate assemblies; Climate emergency; Climate politics; Green New Deal; Just transition; Youth movements; Climate change